A Mechanism-based complementary screening approach for the amelioration and reversal of neurobehavioral teratogenicity - Yanai, Joseph (2009)
The identification of mechanisms and outcomes for neurobehavioral teratogenesis is critical to our ability to develop therapies to ameliorate or reverse the deleterious effects of exposure to developmental neurotoxicants. We established mechanistically-based complementary models for the study of cholinergic systems in the mouse and the chick, using both environmental neurotoxicants (chlorpyrifos, perfluoroalkyls) and drugs of abuse (heroin, nicotine, PCP). Behavioral evaluations were made using the Morris maze in the mouse, evaluating visuospatial memory related to hippocampal cholinergic systems, and imprinting in the chick, examining behavior dependent on cholinergic innervation of the IMHV. In both models we demonstrated the dependence of neurobehavioral deficits on impairment of cholinergic receptor-induced expression, and translocation of specific PKC isoforms. Understanding this mechanism, we were able to reverse both the synaptic and behavioral deficits with administration of neural progenitors. We discuss the prospects for clinical application of neural progenitor therapy, emphasizing protocols for reducing or eliminating immunologic rejection, as well as minimizing invasiveness of procedures through development of intravenous administration protocols.